2013
DOI: 10.1371/journal.pcbi.1003027
|View full text |Cite
|
Sign up to set email alerts
|

Systems Modeling of Molecular Mechanisms Controlling Cytokine-driven CD4+ T Cell Differentiation and Phenotype Plasticity

Abstract: Differentiation of CD4+ T cells into effector or regulatory phenotypes is tightly controlled by the cytokine milieu, complex intracellular signaling networks and numerous transcriptional regulators. We combined experimental approaches and computational modeling to investigate the mechanisms controlling differentiation and plasticity of CD4+ T cells in the gut of mice. Our computational model encompasses the major intracellular pathways involved in CD4+ T cell differentiation into T helper 1 (Th1), Th2, Th17 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 47 publications
2
129
0
Order By: Relevance
“…For the construction of the network, the Boolean functions were defined based on available CD4+ T differentiation models [11][12][13] and experimental data for the reported interactions among a network of more than 90 nodes [Additional file 1: As part of the simplification we assumed that the signal produced by the TCR and its co-factors was active and enough to induce activation and ignored weak interactions as well as input and output nodes.…”
Section: Model Construction and Reductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the construction of the network, the Boolean functions were defined based on available CD4+ T differentiation models [11][12][13] and experimental data for the reported interactions among a network of more than 90 nodes [Additional file 1: As part of the simplification we assumed that the signal produced by the TCR and its co-factors was active and enough to induce activation and ignored weak interactions as well as input and output nodes.…”
Section: Model Construction and Reductionmentioning
confidence: 99%
“…Paradoxically, it has been reported that the reduction of adipose tissue Treg cells seems to both, improve and worsen insulin resistance [37][38][39][40]. This kind of behavior could be linked to an underlying multi-stable dynamic mechanism such as that recently proposed to study CD4+ T cell differentiation and plasticity [11][12][13]. On the other hand, the general metabolic state of an individual also affects CD4+ T cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 A recent report by Carbo et al demonstrates that PPARg activation promotes a phenotype switch from Th17-to-T reg cells and can thereby alleviate colitis. 26 Th17-to-T reg conversion only occurs in lean fat tissue and allows for insulin sensitivity and homeostasis, while Th17 accumulation in adipose tissue is associated with increased insulin resistance. 27 Factors with Dual T reg -and Th17-Promoting Functions…”
Section: T Reg Lineage Is Stablementioning
confidence: 99%